A New Transformation Method of the T2 Spectrum Based on Ordered Clustering—A Case Study on the Pore-Throat Utilization Rule of Supercritical CO2 Flooding in Low Permeability Cores - Yanchun Su; Chunhua Zhao; Xianjie Li; Xiujun Wang; Jian Zhang; Bo Huang; Xiaofeng Tian; Mingxi Liu; Kaoping Song (Applied Sciences)
Nuclear magnetic resonance (NMR) and high-pressure mercury injection (HPMI) have been widely used as common characterization methods of pore-throat. It is generally believed that there is a power function relationship between transverse relaxation time (T2) and pore-throat radius (r), but the segmentation process of the pore-throat interval is subjective, which affects the conversion accuracy. In this paper, ordered clustering is used to improve the existing segmentation method of the pore-throat interval, eliminate the subjectivity in the segmentation process, and obtain a more accurate distribution curve of the pore-throat. For the three kinds of cores with ordinary-low permeability (K > 1 mD), ultra-low permeability (0.1 mD < K < 1 mD), and super-low permeability (K < 0.1 mD), the pore-throat distribution curves of the cores were obtained by using the improved T2 conversion method. Then, the oil and gas two-phase displacement experiment was carried out to investigate the degree of recovery and cumulative gas–oil ratio changes during the displacement process. Finally, the converted T2 spectrum was used to quantify the utilization of different pore sizes. The improved T2 conversion method not only has better accuracy but also is not limited by the pore-throat distribution types (such as unimodal, bimodal, and multi-modal, etc.) and is suitable for any core with measured HPMI pore-throat distribution and an NMR T2 spectrum. Combined with the results of core displacement and the degree of pore-throat utilization, it is found that the potential of miscible flooding to improve the recovery degree is in the order of ordinary-low permeability core (18–22%), ultra-low permeability core (25–29%), and super-low permeability core (8–12%). The utilization degree of immiscible flooding to the <10 nm pore-throat is low (up to 35%), while miscible flooding can effectively use the <3.7 nm pore-throat (up to 73%). The development effect of supercritical CO2 flooding on K < 0.1 mD reservoirs is not good, the seepage resistance of CO2 is large, the miscible flooding makes it difficult to improve the recovery degree, and the utilization effect of pore-throat is poor.